Investigation of the performance of a thermosyphon pin fin heat sink - Sun, Jianchun. (2008)
An analytical, numerical and experimental investigation was conducted to examine the performance of the thermosyphon pin fin heat sink which consists of a flat plate with area of 40 x 40 mm2 and thickness of 10 mm as the evaporator and an array of 5 x 5 small water/copper tubes with inner diameter of 2.5 mm and length of 58 mm as the condenser.